2016
DOI: 10.3111/13696998.2016.1138962
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of brain metastasis among lung cancer patients in the United States

Abstract: Development of brain metastasis among lung cancer patients is associated with a substantial economic burden to payers, patients, and employers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…The search identified 3945 unique citations (PubMed (n = 2891), Web of Science (n = 775), CINAHL (n = 180), and PsycINFO (n = 99)) with 31 studies meeting our inclusion criteria (Table 2) [8, 18, 20, 21, 26, 29-33, 36-38, 40, 41, 43], 5 studies focused on breast cancer [19,25,28,35,42,44] and 2 included multiple myeloma patients [22,45]. The other studies focused on bladder [39], prostate [23], colorectal [24], lung [27], head and neck cancer [34], and bone marrow transplant patients [17]. Time since diagnosis ranged from a mean of 8.4 months before diagnosis [27] until a mean of 13 years after diagnosis [19] often had a broad range, and sometimes was not reported at all.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search identified 3945 unique citations (PubMed (n = 2891), Web of Science (n = 775), CINAHL (n = 180), and PsycINFO (n = 99)) with 31 studies meeting our inclusion criteria (Table 2) [8, 18, 20, 21, 26, 29-33, 36-38, 40, 41, 43], 5 studies focused on breast cancer [19,25,28,35,42,44] and 2 included multiple myeloma patients [22,45]. The other studies focused on bladder [39], prostate [23], colorectal [24], lung [27], head and neck cancer [34], and bone marrow transplant patients [17]. Time since diagnosis ranged from a mean of 8.4 months before diagnosis [27] until a mean of 13 years after diagnosis [19] often had a broad range, and sometimes was not reported at all.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The other studies focused on bladder [39], prostate [23], colorectal [24], lung [27], head and neck cancer [34], and bone marrow transplant patients [17]. Time since diagnosis ranged from a mean of 8.4 months before diagnosis [27] until a mean of 13 years after diagnosis [19] often had a broad range, and sometimes was not reported at all. Sample sizes ranged from 129 [19] to 16,771 [30] participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies of North American insurance claims databases have evaluated the economic burden of brain metastases in patients with primary lung cancer and have shown that direct health costs increase around fourfold following diagnosis of brain metastases. 8 9 In particular, use of stereotactic brain surgery may markedly increase the cost of treatment. 10 However, since the cost of management of lung cancer rises substantially following evolution to the metastatic stage, regardless of the site of metastasis, 11 it is not clear how much of the extra cost determined in these studies is inherent to management of metastases specifically arising in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In these molecular subgroups where the incidence of brain metastases is high, further clarification of response to ICIs will be important. When brain metastases develop, the cost of patient care rises significantly (84). It is unlikely that use of ICIs without better patient selection will be cost effective in treating an overall poor prognostic cohort of patients.…”
Section: N I V O L U M a B H A S A L S O D E M O N S T R A T E D A C mentioning
confidence: 99%